Tensile Strength and Elongation Characteristics of Bioplastics Made from Cilembu Sweet Potatoes Starch with Various Types of Plasticizers - Lailatin Nuriyah; Gancang Saroja; Muhammad Ghufron; Arvi Razanata; Nova Fathur Rosid (Natural B, Journal of Health and Environmental Sciences, 2018)
Nowadays, many researchers are doing research in the field of degradable plastics with replacing synthetic polymers with natural synthetics for resulting the bioplastics. A natural raw that often used by the researcher is starch. For producing the bioplastic, the starch is mixed with plasticizers. The aims of this research are for observing the influences of the plasticizer to the tensile strength and elongation of bioplastic that made from the starch of Cilembu sweet potato. The plasticizers that used in this research are glycerol, sorbitol, and egg white. The bioplastics are produced in four stages, such as starch producing, heating and adding of the plasticizers, casting, and measuring the tensile strength and elongation. In the producing process of starch, firstly, the potato was destroyed, then it was blended with fresh water, after that it was settled down, followed by filtering and drying. The next stage was heating and adding of the plasticizers. The process of glycerol and sorbitol adding did at 45 oC while the heating process performed until gelatinization temperature was reached. However, while using egg white as a plasticizer, the process was started at 50 oC. After that, the casting stage was done, followed by the last stage, the testing of bioplastic samples. The results of the experiment show that the variation of the plasticizer affects the tensile strength and elongation of the bioplastic. The addition of plasticizer as many as 2,8% reduces the tensile strength of the bioplastic by 90% for glycerol and 75% for sorbitol. Whereas with the addition of the egg white, the tensile strength of the bioplastic is increased to 49%. For elongation property of the bioplastic, both glycerol and sorbitol as many as 2,8% will decrease the elongation value 32,8% and 16,1% respectively. However, the elongation values of the bioplastic fluctuated for the white egg plasticizer.